Instability of parasitic capacitance in T-shape-gate enhancement-mode AlGaN/GaN MIS-HEMTs. (1st March 2022) - Bi, Lan; Yao, Yixu; Jiang, Qimeng; Huang, Sen; Wang, Xinhua; Jin, Hao; Dai, Xinyue; Xu, Zhengyuan; Fan, Jie; Yin, Haibo; Wei, Ke; Liu, Xinyu
Abstract: Parasitic capacitances associated with overhangs of the T-shape-gate enhancement-mode (E-mode) GaN-based power device, were investigated by frequency/voltage-dependent capacitance–voltage and inductive-load switching measurements. The overhang capacitances induce a pinch-off voltage distinguished from that of the E-mode channel capacitance in the gate capacitance and the gate–drain capacitance characteristic curves. Frequency- and voltage-dependent tests confirm the instability caused by the trapping of interface/bulk states in the LPCVD-SiN x passivation dielectric. Circuit-level double pulse measurement also reveals its impact on switching transition for power switching applications.